Graduate employability and higher education`s contributions to human resource development in sport business before and after COVID-19 - Sato, S.; Kang, T.-A.; Daigo, E.; Matsuoka, H.; Harada, M. (Journal of Hospitality, Leisure, Sport & Tourism Education, 2021)
The sport labor market`s needs are susceptive to environmental factors. The situation regarding COVID-19 has particularly been influential in altering employment and education policies. The purpose of this research was twofold (1) to understand the graduate employability (i.e., hard and soft skills): and contributions that higher education institutions can make to produce human resources and (2) to identify the differences regarding the above factors before and after COVID19. The results of Delphi study with executive-level experts in sport business identified various hard/soft skills and higher education`s potential contributions. Moreover, experts` expectations are found to be intensified after the COVID-19 outbreak.